Prospective effects of mindfulness on anxiety and depressive symptoms may be spurious: Simulated reanalysis of a meta-analytic cross-lagged panel analysis. - Kimmo Sorjonen; Bo Melin (PLoS ONE)
A recent meta-analysis claimed decreasing prospective effects of acting with awareness and non-reacting, two facets of dispositional mindfulness, on subsequent anxiety and depressive symptoms. However, the meta-analytic cross-lagged effects were estimated while adjusting for a prior measurement of the outcome variable and it is known that such adjusted cross-lagged effects may be spurious due to correlations with residuals and regression to the mean. We fitted competing models on simulations of the same meta-analytic data and found that prospective effects of the mindfulness facets on anxiety and depressive symptoms probably were spurious. It is important for researchers to be aware of limitations of adjusted cross-lagged effects, meta-analytically estimated or not, in order not to overinterpret findings.